Analysis of ICH-Q3D Endorsed Elemental Impurities in Macrolide Antibiotics by ICP-MS - Mathesan, Ravisankar; Sekar, Alexandar; Raju, Senthil Kumar; Mohan, Kumar; Sri, Venkateswarlu Bendi (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The objective of this study was to determine the amount of twenty-three elemental impurities in Azithromycin API. A rapid, selective, precise, accurate and sensitive approach for detecting elemental impurities in Azithromycin API was developed and validated using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Background: Conventional analytical methods used in pharmacopoeia’s are less sensitive and accurate to detect heavy metal impurities. Concerning this issue, a new inductively coupled plasma mass spectrometry-based method was developed and validated as a different choice to investigate the Elemental impurities in an Azithromycin API sample. Materials and Methods: In the present research work, test samples were prepared with microwave supported acid digestion. Results: After a sequence of trails, the mixture of nitric acid, hydrochloric acid, and hydrogen peroxide (4 mL: 1 mL: 0.5 mL) with the accepted recovery range was chosen for the Azithromycin API's digestion. Conclusion: According to ICH and USP 233 guidelines, the proposed technique was successfully validated using ICP-MS for linearity, precision, accuracy, LOD, LOQ, and ruggedness.
Keywords: Azithromycin API; Elemental Impurities; Inductively coupled plasma mass spectrometry; Method Development; ICH Guidelines